1957
DOI: 10.1042/bj0670435
|View full text |Cite
|
Sign up to set email alerts
|

The molecular weights of the proteins of normal and nephrotic sera and nephrotic urine, and a comparison of selective ultrafiltrates of serum proteins with urine proteins

Abstract: AN ELECTRONIC COLLOID OSMOMETER 435 2. Measurements could be made 30 min. after placing a solution in the instrument. 3. Ten observations on each of a series of seven solutions of bovine plasma albumin were made, in two osmometers. The S.E. of the means of the observations ranged from 0-017 to 0-048 cm. H20 with osmotic pressures ranging from 1 9 to 13*7 cm. H20. 4. The value for molecular weight of bovine plasma albumin derived by various methods from these results ranged from 66 600 to 68 800. The authors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1958
1958
1970
1970

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The concept of selective permeability introduced by Hardwicke and Squire (14) has been supported by the results of paper electrophoresis (15), of gel filtration (16,17), and of semiquantitative imminunodiffusion (18), but the absolute value of the content of each individual plasma protein in normal urine is not avaiable. Only albumin has been quantitatively determined in human urine (19,20), with the results being expressed in terms of milligrams of protein excreted per 24 hr.…”
Section: Introductionmentioning
confidence: 85%
“…The concept of selective permeability introduced by Hardwicke and Squire (14) has been supported by the results of paper electrophoresis (15), of gel filtration (16,17), and of semiquantitative imminunodiffusion (18), but the absolute value of the content of each individual plasma protein in normal urine is not avaiable. Only albumin has been quantitatively determined in human urine (19,20), with the results being expressed in terms of milligrams of protein excreted per 24 hr.…”
Section: Introductionmentioning
confidence: 85%
“…The 1 Behringwerke, A. G., Marburg-Lahn, Germany. 2 Hyland Laboratories, Los Angeles, Calif. goat antisera were prepared by using isolated and purified serum constituents as immunizing antigens. Several manipulations were required to obtain relatively pure preparations, but the yields frequently were poor (11).…”
Section: Methodsmentioning
confidence: 99%
“…Although no recognizable structural abnormality has been defined to indicate a pathway of protein excretion, the permeability of the glomerular membrane, under conditions of moderate and heavy proteinuria, has been interpreted in terms of distribution of "pore size" (1)(2)(3). This concept suggests the presence of "defects" or "pores" in the glomerular membrane of such dimensions that permit the passage of these proteins into the glomerular filtrate.…”
mentioning
confidence: 99%
“…(Received for publication 20 July 1970) Physiological studies (1)(2)(3)(4) have indicated that increased glomerular permeability is the major cause of proteinuria in human and experimental nephrosis, but the ultrastructural basis for such protein leakage is poorly understood. Previous morphological studies using ferritin (tool wt 500,000) (5,6) have shown that the glomerular basement membrane becomes more permeable to this particle in experimental nephrosis induced by the aminonucleoside of puromycin (7), and it has been suggested that a basement membrane lesion is the primary cause of proteinuria (6).…”
mentioning
confidence: 99%